Dynamic SUMOylation Is Linked to the Activity Cycles of Androgen Receptor in the Cell Nucleus - Rytinki, Miia (American Society for Microbiology, 2012)
Despite of the progress in the molecular etiology of prostate cancer, the androgen receptor (AR) remains the major druggable target for the advanced disease. In addition to hormonal ligands, AR activity is regulated by posttranslational modifications. Here, we show that androgen induces SUMO-2 and SUMO-3 (SUMO-2/3) modification (SUMOylation) of the endogenous AR in prostate cancer cells, which is also reflected in the chromatin-bound receptor. Although only a small percentage of AR is SUMOylated at the steady state, AR SUMOylation sites have an impact on the receptor's stability, intranuclear mobility, and chromatin interactions and on expression of its target genes. Interestingly, short-term proteotoxic and cell stress, such as hyperthermia, that detaches the AR from the chromatin triggers accumulation of the SUMO-2/3-modified AR pool which concentrates into the nuclear matrix compartment. Alleviation of the stress allows rapid reversal of the SUMO-2/3 modifications and the AR to return to the chromatin. In sum, these results suggest that the androgen-induced SUMOylation is linked to the activity cycles of the holo-AR in the nucleus and chromatin binding, whereas the stress-induced SUMO-2/3 modifications sustain the solubility of the AR and protect it from proteotoxic insults in the nucleus.